ALT-FISH quantifies alternative lengthening of telomeres activity by imaging of single-stranded repeats. Issue 11 (21st February 2022) - Frank, Lukas; Rademacher, Anne; Mücke, Norbert; Tirier, Stephan M; Koeleman, Emma; Knotz, Caroline; Schumacher, Sabrina; Stainczyk, Sabine A; Westermann, Frank; Fröhling, Stefan; Chudasama, Priya; Rippe, Karsten
Abstract: Alternative lengthening of telomeres (ALT) occurs in ∼10% of cancer entities. However, little is known about the heterogeneity of ALT activity since robust ALT detection assays with high-throughput in situ readouts are lacking. Here, we introduce ALT-FISH, a method to quantitate ALT activity in single cells from the accumulation of single-stranded telomeric DNA and RNA. It involves a one-step fluorescent in situ hybridization approach followed by fluorescence microscopy imaging. Our method reliably identified ALT in cancer cell lines from different tumor entities and was validated in three established models of ALT induction and suppression. Furthermore, we successfully applied ALT-FISH to spatially resolve ALT activity in primary tissue sections from leiomyosarcoma and neuroblastoma tumors. Thus, our assay provides insights into the heterogeneity of ALT tumors and is suited for high-throughput applications, which will facilitate screening for ALT-specific drugs.